IMPROVED CROSS-MODEL MODAL STRAIN ENERGY METHOD FOR STRUCTURAL DAMAGE LOCALIZATION - ZHANG YaRu; MA Jun; WU XiaoShun (Jixie qiangdu)
In order to improve the accuracy of structural damage localization, a method to locate structural damages is proposed by combining the cross-model modal strain energy and the wavelet analysis(WA). Firstly, indices based on cross-modelmodal strain energy of all elements have been calculated. Secondly, the wavelet analysis is conducted on the sequence composed of the calculated indices of all elements, with high-frequency detail coefficients extracted to form the improved damage index. Finally, damage locations are judged according to the improved index. A planar truss is taken as the numerical example, with the Monte Carlo analysis carried out in consideration of 5% noise level. The result shows that the improved index is more robust to resist noise interference and can better indicate damage locations.